Soil moisture estimation of drained peat area using TOPSAR data - Hashim, Mazlan; Sim, Peter Hock Seng; Wan Kadir, Wan Hazli; Ngap, Dollah Salam (2001)
Three empirical and theoretical radar backscatter models were examined in this study to characterise radar backscatter of TOPSAR data over coastal lowland of Sadong Simunjan River Basin, Sarawak, Malaysia. The main objective of this paper is to analyse the relationship between radar backscatter of TOPSAR data to degree of wetness of drained peat-land. The analysis of these models were examined using varying terrain-and-sensor related parameters namely surface roughness, dielectric constant, incidence angle, polarization and frequency, respectively. The results of this study indicate good relationship between moisture content and radar backscatter (RMSE < 5.0) in empirical model. However, this relationship is found rather restricted in the theoretical models due to its sensitivity to very moist to wet nature of the study area.